Processed line aerogravity data from the FISS 2016 surveys covering the Filchner and Halley Ice Shelves, and the English Coast (western Palmer Land), West Antarctica (2016/2017) - Becker, David; Jordan, Tom; Robinson, Carl; Corr, Hugh (NERC EDS UK Polar Data Centre, 2021)
Three separate airborne radar surveys were flown during the austral summer of 2016/17 over the Filchner Ice Shelf and Halley Ice Shelf (West Antarctica), and over the outlet glacier flows of the English Coast (western Palmer Land, Antarctic Peninsula) during the Filchner Ice Shelf System (FISS) project. This project was a NERC-funded (grant reference number: NE/L013770/1) collaborative initiative between the British Antarctic Survey, the National Oceanography Centre, the Met Office Hadley Centre, University College London, the University of Exeter, Oxford University, and the Alfred Wenger Institute to investigate how the Filchner Ice Shelf might respond to a warmer world, and what the impact of sea-level rise could be by the middle of this century. The 2016/17 aerogeophysics surveys acquired a total of ~26,000 line km of aerogeophysical data. The FISS survey consisted of 17 survey flights totalling ~16,000 km of radar data over the Support Force, Recovery, Slessor, and Bailey ice streams of the Filchner Ice Shelf. The Halley Ice Shelf survey consisted of ~4,600 km spread over 5 flights and covering the area around the BAS Halley 6 station and the Brunt Ice Shelf. The English Coast survey consisted of ~5,000 km spread over 7 flights departing from the Sky Blu basecamp and linking several outlet glacier flows and the grounding line of the western Palmer Land, including the ENVISAT, CRYOSAT, GRACE, Landsat, Sentinel, ERS, Hall, Nikitin and Lidke ice streams. Our Twin Otter aircraft was equipped with dual-frequency carrier-phase GPS for navigation, radar altimeter for surface mapping, wing-tip magnetometers, an iMAR strapdown gravity system, and a new ice-sounding radar system (PASIN-2). We present here the processed line aerogravity data collected using the iMAR strapdown gravity system mounted in the BAS aerogeophysically equiped Twin Otter aircraft. Data are provided as XYZ ASCII line data. : Gravity results for the 2016/2017 FISS campaign, taken from the iMAR iNAV-RQH1003 sensor (total: 24 flights). The IMU/GNSS-strapdown gravity data processing was done by David Becker, Physical and Satellite Geodesy, TU Darmstadt, with a processing software that was developed at this institute. The cross-over-residuals suggest a data precision (unlevelled) of approx. 1.7 mGal. No terrestrial gravity ties were available for this campaign, so the determination of the absolute gravity level was difficult: - For flights F06-F18, the absolute value was determined by a comparison against existing IceBridge gravity data (uncertainty of this levelling and the IceBridge gravity level itself is expected to be around 3 mGal). - For flights F19-F23 and F25-F29, the absolute value was determined just using the IMU measurements, assuming that the temperature-corrected residual accelerometer biases were the same during the campaign (error of this assumption: approx 3 mGal). The positions (lat/lon/height) refer to the centre of observations of the iMAR-RQH IMU (the intersection point of its three accelerometers). The flights are now grouped by survey area (Recover, Slessor, Bailey = FISS). NOTE there is no Support Force gravity as the sensor was not on-board. The columns are: 1: Line or flight number 2: Date (YYYY/MM/DD) 3: Time (HH:MM:SS) 4: Latitude in degrees 5: Longitude in degrees 6: Elevation - Ellipsoidal Height (WGS84) in metres 7: Free Air anomaly [mGal] - Gravity disturbance w.r.t. GRS80 normal gravity [mGal] : The data were collected using an iMAR strapdown gravity system.